Mass spectrometry analysis of protein blood extracts of animals with experimental brucellos - D. V. Ulshina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2019)
Aim. The aim of the present research was to study the possibility of direct detection of the causative agent of brucellosis in a biomaterial under experimental conditions via the MALDI-TOF MS method using Mass-Up program resources and a set of packages for open-source statistical software R. Materials and methods. We used laboratory mice infected with the causative agents of Brucellosis (strains B. melitensis 548, B. abortus 544, B. suis 1330) as models. Protein profiling was performed on a MALDI-TOF Microflex «Bruker Daltonics» mass spectrometer. Results. The bioinformatic-statistical approach used for analyzing MALDI-TOF mass spectra allows to carry out a direct detection of Brucella in the biomaterial; besides, it is possible to determinate their species via the identification of a group of biomarkers. Conclusion. It was experimentally confirmed that the protein profiles of the blood extracts of infected animals contain 11 markers, including 6 genus specific for Brucella spp., which can be associated with Brucella infection.